Deep Vein Thrombosis Accompanied by Acute Bacterial Infection, Hypercholesterolemia and Grade I Obesity in a 20-Year-Old Man in a Hospital - Putri Unggun Az Zahra; Shelvi Febrianti; Kusmardi Kusmardi (INDOGENIUS, 2026)
Backgorund: Deep vein thrombosis (DVT) is a condition in which thrombus forms in the inner veins, especially the lower legs, which can cause serious complications in the form of pulmonary embolism. Risk factors for DVT can include immobilization, hemostasis disorders, metabolic disorders, and systemic diseases that affect vascularization. Method: In certain cases, DVT can appear at the same time as other diseases that aggravate the clinical course. It was reported that a 20-year-old man with the main complaint was pain and swelling in the lower limbs since a few days before being admitted to the hospital. Patients also complain of high fever and bleeding gums. Physical examination found that the lower limbs were swollen, tender, and warm. Results: The results of the supporting examination showed the presence of thrombus in the profunda vein through doppler ultrasound, so the diagnosis of DVT was established. Hematological examinations showed neutrophilia, thrombocytopenia, lipid profiles showed increased total cholesterol, while ECG examinations supported the presence of myocardial ischemia. Patients were managed with a multidisciplinary approach: antibiotics, anticoagulants, and risk factor control. Conclusion: This case illustrates the complexity of treating DVT in young patients with high-risk comorbidities, as well as emphasizing the importance of early detection and individualized therapy to prevent further complications.